Creative and innovative teaching practices during COVID-19 Movement Control Order (MCO) / Jamal Othman, Azlina Mohd Mydin and Naemah Abdul Wahab - Othman, Jamal; Mohd Mydin, Azlina; Abdul Wahab, Naemah (Unit Penerbitan JSKM, UiTM Pulau Pinang, 2020)
World Health Organisation (WHO) has declared COVID-19 as a pandemic disease. The number of infected people with COVID-19 has increased abruptly over the world. Many countries have declared lockdown and Movement Control Order (MCO) to control the transmission of the virus. The most affected ministry is the Education Ministry whereby all schools, colleges and universities have been instructed to close. Teachers and lecturers were advised to conduct their classes through non face to face or e-learning methods. Although it was sudden decision made by government and quite difficult to be faced or accepted by all instructors, everybody has to accept this is as the new norms. Several methods and technologies have been introduced to help the instructors delivering their lectures effectively to students. The instructors were also encouraged to make use of available technologies and implement free resources that are accessible from the Internet without incurring additional expenses so that the instructors and leaners are not burdened and stressed. Understanding the lectures delivered to the learners and effectiveness of the technology used are among the important elements in online teaching and learning (T&L) methods. This paper shares the experiences of several instructors applying the best practices of teaching and learning (T&L) technologies during the Movement Control Order (MCO) period.